[Cal Poly cross country runners] - Jim Alvernaz::::::photographer::: (1978)
A pack of Cal Poly cross country runners at a meet. Photograph was taken by Jim Alvernaz and published in the Mustang Daily on November 14, 1978. Runners pictured include, from left to right, John Capriotti, Dan Aldridge, Jim Schankel, Mitch Kingery, and Manny Bautista.